(untitled) (REMUNOM, 2026)
The Rural Education Degree Program (Licenciatura em Educação do Campo – LEDOC) represents a critical public policy initiative for teacher education in rural territories, grounded in principles of territoriality, interdisciplinarity, and alternating training periods. In recent years, however, the rapid expansion of Distance Education (Educação a Distância – EAD) in Brazilian higher education has purportedly reshaped enrollment dynamics, particularly in teacher-education programs offered by public universities. Despite ongoing debate, empirical analyses remain scarce and, in most cases, lack statistical examination. This study investigated the influence of the accumulated supply of EAD seats on the enrollment rate of the LEDOC program at the Federal University of Piauí (UFPI) between 2014 and 2025. We used institutional data on the number of seats offered and filled in the first admission call, as well as consolidated information on public calls for applications and the expansion of EAD. Data were analyzed through descriptive statistics and simple linear regression to assess the relationship between variables. Results indicate that approximately 42% of the decline in LEDOC enrollment can be attributed to the cumulative increase in EAD seats during the 2014 - 2025 period, revealing a significant negative impact of the remote modality on demand for the in-person degree. However, additional factors - outside the scope of this study - almost certainly contributed to the phenomenon, including the closure of rural schools, the weakening of public policies targeting Rural Education, digital inequality, and adverse socioeconomic conditions faced by rural students. We conclude that, although the expansion of EAD plays an important role in democratizing access to higher education, it requires coordinated public and institutional planning to prevent internal competition with strategic academic programs. We recommend the implementation of integrated student-support policies, balanced regulation between modalities, and the strengthening of rural schools and other targeted public policies to ensure the continuity and social relevance of LEDOC.